Pitavastatin Induces Cancer Cell Apoptosis by Blocking Autophagy Flux - Tilija Pun, Nirmala; Lee, Naeun; Song, Sang-Hoon; Jeong, Chul-Ho (Frontiers in Pharmacology, 2022)
Statins, a class of lipid-lowering drugs, are used in drug repositioning for treatment of human cancer. However, the molecular mechanisms underlying statin-induced cancer cell death and autophagy are not clearly defined. In the present study, we showed that pitavastatin could increase apoptosis in a FOXO3a-dependent manner in the oral cancer cell line, SCC15, and the colon cancer cell line, SW480, along with the blockade of autophagy flux. The inhibition of autophagy by silencing the LC3B gene reduced apoptosis, while blockade of autophagy flux using its inhibitor, Bafilomycin A1, further induced apoptosis upon pitavastatin treatment, which suggested that autophagy flux blockage was the cause of apoptosis by pitavastatin. Further, the FOXO3a protein accumulated due to the blockade of autophagy flux which in turn was associated with the induction of ER stress by transcriptional upregulation of PERK-CHOP pathway, subsequently causing apoptosis due to pitavastatin treatment. Taken together, pitavastatin-mediated blockade of autophagy flux caused an accumulation of FOXO3a protein, thereby leading to the induction of PERK, ultimately causing CHOP-mediated apoptosis in cancer cells. Thus, the present study highlighted the additional molecular mechanism underlying the role of autophagy flux blockade in inducing ER stress, eventually leading to apoptosis by pitavastatin.